APLIKASI PENGGUNAAN ZPT PADA PERBANYAKAN RHODODENDRON JAVANICUM BENN. (BATUKAU, BALI) SECARA VEGETATIF (SETEK PUCUK) - PUTRI, DYAN M.S.; SUDIATNA, I NYOMAN (Jurnal Biologi Udayana; Vol 13 No 1 (2009): JURNAL BIOLOGI, 2009)
Rhododendron javanicum Benn. has a potential use as an ornamental plant and medicine. The aim of the research was to find out the effect of plant growth regulator on the vegetative growth of Rhododendron javanicum Benn. (Batukau, Bali). The experiment was designed in Cluster Random Sampling, which the groups I consist of concentrations of plant growth regulators (Rootone F: 0 ppm (control), 100 ppm, 150 ppm, 200 ppm). Sampling time treatment of 30, 60, 90 and 120 days after planted were used for groups II. Each treatment was replicated three times. The life materials used in this experiment were shoot cuttings of Rhododendron javanicum Benn. (Batukau, Bali) with equal numbers of leaves (5-7 leaves) and were planted in the pot using media types of Asplenium roots: Cyathea roots:charcoal (2:2:1). Observed parameters were the numbers of shoots, plants height and the environmental factors (temperature and humidity). Analysis of variance (the numbers of shoots) showed that for each concentration the number of shoots was differ significantly between time treatments. The variant analysis of plant heights showed that for each concentration the plant height was not differ significantly between time treatments. The temperature during the research is 15,31 – 23,76 oC and humidity is 56,20 – 85,34 %. From this research, it can be concluded that the vegetative growth of Rhododendron javanicum Benn. (Batukau, Bali) was influenced by time treatment but not by concentration of plant growth regulator. For better results it is suggested to increase the concentrations of plant growth regulator.
Keywords: Rhododendron javanicum Benn. (Batukau, Bali); growth; propagation; vegetative